Preparation of nanoliposomes containing Hyssopus officinalis L. and Eryngium caeruleum M.Bieb extracts and investigate their antimicrobial and antimicrobial effects - Marjan Nouri (Institue of Medicinal Plants, ACECR, 2020)
Background: The general tendency of society in the use of natural extracts as antimicrobial, antioxidant and preservative compounds has increased in recent years. Objective: The purpose of this study is to improve the functional properties of two native plants (Hyssopus officinalis and Eryngium caeruleum M.Bieb) of the country that was accomplished by comparing the increasing stability of the antimicrobial and antioxidant properties of nanoliposomes containing their extracts with the control compounds (free extracts). Methods: Aqueous extraction was performed after identification of both plants and nanoliposomes of H. officinalis, E. caeruleum and their compound were produced based on thin- film hydration method. Tests of encapsulation efficiency, loading capacity, particle size with dynamic light scattering, zeta potential with zetasizer, antioxidant activity by the DPPH radical scavenging method and antimicrobial property were determined by well method. Results: Nanoliposomes containing E. caeruleum extract had significantly higher loading capacity (5.17%) and encapsulation efficiency (5.23%). The mean size of nanoliposome particles of E. caeruleum extract was significantly higher (21.54 nm) than other samples. The antioxidant activity of the extracts was increased after encapsulation in the nanoliposome, and the EC50 of the nanoliposomal E. caeruleum extract was decreased to 14.27 (μg/ml). Among the microsatellites, Streptococcus iniae (43.19 mm) and Staphylococcus aureus (38.18 mm), respectively, showed a higher growth inhibition compared to other bacterias in the presence of nanoliposomes containing H. officinalis and E. caeruleum extracts. Conclusion: Nanoliposomes containing Hyssopus officinalis and E. caeruleum extracts can best increase the functional properties of these medicinal plants and are recommended for industrial application.